2015
DOI: 10.1111/liv.12746
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA HOTTIP is frequently up‐regulated in hepatocellular carcinoma and is targeted by tumour suppressive miR‐125b

Abstract: HOTTIP is a novel oncogenic lncRNA, which negatively regulated by miR-125b. Overexpression of HOTTIP contributes to hepatocarcinogenesis by regulating the expression of its neighbouring protein-coding genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 26 publications
4
92
0
Order By: Relevance
“…In ovarian cancer, miR-125a and miR-125b could inhibit ovarian cancer cell migration, invasion and proliferation by regulating EIF4E-binding protein 1 (24). A study on HCC revealed that the tumor suppressive miR-125b could negatively regulate the expression of long non-coding RNA HOTTIP (25), and low expression of miR-125b was a prognostic marker for poor disease status and outcome (13). It was also revealed that miR-125b could suppress gastric cancer proliferation and invasion by targeting MCL1, and the low expression of miR-125b was associated with advanced clinical stage, lymph node metastases and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovarian cancer, miR-125a and miR-125b could inhibit ovarian cancer cell migration, invasion and proliferation by regulating EIF4E-binding protein 1 (24). A study on HCC revealed that the tumor suppressive miR-125b could negatively regulate the expression of long non-coding RNA HOTTIP (25), and low expression of miR-125b was a prognostic marker for poor disease status and outcome (13). It was also revealed that miR-125b could suppress gastric cancer proliferation and invasion by targeting MCL1, and the low expression of miR-125b was associated with advanced clinical stage, lymph node metastases and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies about miR-125b indicated that miR-125b acted as a tumor suppressor in osteosarcoma, ovarian cancer, hepatocellular carcinoma (HCC) and gastric cancer (15,(24)(25)(26). In ovarian cancer, miR-125a and miR-125b could inhibit ovarian cancer cell migration, invasion and proliferation by regulating EIF4E-binding protein 1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of HOTTIP significantly suppressed the expression of a number of HOXA genes Moreover, in human HCCs, HOTTIP expression negatively correlated with that of miR-125b, which is a post-transcriptional regulator of HOTTIP [31] (Figure 1e). miR-141 and miR-148a show an inhibitory effect on the expression of DNA methyltransferase 1 (DNMT-1) and thus induces the overexpression of MEG3 [32] (Figure 2c).…”
Section: Interaction With Mirnasmentioning
confidence: 99%
“…It has been reported to directly bind the adaptor protein WD repeat-containing protein 5 (WDR5) and to target WDR5/mixed lineage leukemia complexes, driving histone H3 lysine 4 trimethylation and gene transcription of distal HOXA genes (13). Several previous studies have reported that, compared with normal adjacent tissues (NATs), HOTTIP expression was significantly increased in skin, hepatocellular, pancreatic, lung and tongue squamous cell cancer tissues (14)(15)(16)(17)(18)(19)(20). HOTTIP may be involved in the progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%